A local criterion for ductile fracture under low-triaxiality axisymmetric stress states. (January 2017) - Smith, Christopher; Kanvinde, Amit; Deierlein, Gregory
Highlights: Ductile fracture in steel is predicted at high and low triaxiality. The criterion is validated with computational simulations and 352 tests. Uncertain and incongruent data are accommodated by the probabilistic criteria. A ductile fracture cutoff is found at a stress triaxiality of zero. Abstract: A local criterion is presented for ductile fracture of metals under a wide range of stress triaxiality. In contrast to previous criteria, whose accuracy is generally limited to the narrower stress ranges over which they were originally validated, the proposed criterion is rigorously supported through (1) hypothesis testing against 352 experiments conducted during previous studies of high- and low-triaxiality fracture and (2) micromechanical models of the underlying fracture process. The proposed criterion implies a low-triaxiality fracture cutoff at a stress triaxiality of approximately zero, which is supported by experimental test data.